Analisis Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Beban Kerja Terhadap Kinerja Karyawan Non Medis Di Rumah Sakit: (Study on Employees of Harapan Mulia Tigaraksa Mother and Child Hospital) - Saefullah Saefullah; Haniyyah Haniyyah; Vina Afianti; Ichsan Prastya Firmansyah; Aip Sarifudin; Mira Apriana Markus; Francisca Sestri Goestjahjanti; Winanti Winanti; Karnawi Kamar; Akhmad Farhan (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
Leadership style, work environment, and workload are very important in determining employee performance success, and to date, many companies still pay little attention to these three things. This study aims to analyze the influence of leadership style, work environment, and workload on the performance of non-medical employees at Harapan Mulia Tigaraksa Mother and Child Hospital. The participants in this research included 50 staff non-medical at Harapan Mulia Mother and Child Hospital, determined through the Slovin sampling method. Information was gathered by handing out questionnaires completed by non-medical staff at the Harapan Mulia Mother and Child Hospital, which was chosen as the sample. This research employs a Likert scale. The quantitative analysis conducted by the author includes validity testing, reliability testing, classical assumption testing, correlation analysis testing, determination coefficient testing, regression analysis testing, and hypothesis testing using t-tests (partial) and F-tests (simultaneous) at a significant.